Homework in the Subject of Serbian Language and Literature with a Psychological and Pedagogical Review - Ana Krstić (Društvene i Humanističke Studije, 2019)
The subject of this paper is homework assignments in the teaching of Serbian language and literature,with special emphasis on the forms, types and appropriateness of tasks in the methodical sense.Considering three parts of the Serbian Language and Literature course, the types of homework will bestudied in each of the teaching areas, ie language, literature and speaking and writing. The adequacy oftasks is reflected in their complexity, weight, in proportion to the age and class of students from the youngest primary schoolers to the higher grades of elementary school. In addition, relevant psychologicaland pedagogical research on the development of child psyche and mental abilities will be considered. Through a three-part division of the course, examples of domestic tasks that stimulate creative thinking,i.e. which are of equal or approximate use, as well as tasks done in school will be presented. Nonproductive tasks based on reproduction or quantitative overload appear as counter-agents. The goal is also to determine to what extent and when the homework assigns its theoretically presumedpurpose in the teaching of Serbian language and literature, and when and how often it is desirable totransform established and non-creative burden some homework assignments, or completely eliminate them.